Effect of urea inclusion in diets containing corn dried distillers grains on feedlot cattle performance, carcass characteristics, ruminal fermentation, total tract digestibility, and purine derivatives-to-creatinine index - Ceconi, Irene; Ruiz-Moreno, M.J.; DiLorenzo, Nicolas; DiCostanzo, A.; Crawford, G.I. (American Society of Animal Science, 2019)
Increased availability of rapidly fermentable carbohydrates and a great proportion of corn-derived CP in the diet may result in a degradable intake protein (DIP) deficit. Therefore, ruminal DIP deficit may result from high dietary inclusion of processed corn grain and small to moderate inclusion of corn distillers grains (DG). Two experiments were conducted to evaluate the effect of increasing dietary DIP concentration through the inclusion of urea on feedlot cattle performance, carcass characteristics, ruminal fermentation, total tract digestibility, and purine derivatives-to-creatinine (PDC) index. In Exp. 1, 42 steers (428 ± 5 kg initial BW) were assigned randomly to 1 of 3 diets containing (DM basis) 0 (control [CON]), 0.4 (low urea [LU]), or 0.6% urea (high urea [HU]) to provide 6.4, 7.5, or 8.0% dietary DIP, respectively, and 12% high-moisture corn (HMC), 20% corn dried DG with solubles (DDGS), 10% ryegrass haylage, 2.9% dry supplement, and dry-rolled corn (DRC). Steers were fed ad libitum once daily using a Calan gate system. Carcass-adjusted final BW and DMI were similar among treatments (P ≥ 0.58). Carcass-adjusted ADG was greater (P ≤ 0.04) for the HU diet compared with the LU and CON diets and was similar (P = 0.73) between the LU and CON diets. Carcass-adjusted G:F was greater (P = 0.03) for the HU diet compared with the LU diet, tended (P = 0.09) to be greater compared with the CON diet, and was similar (P = 0.61) between the LU and CON diets. Carcass characteristics were similar (P ≥ 0.34) among treatments. In Exp. 2, 4 ruminally cannulated steers (347 ± 18 kg initial BW) were randomly assigned to a replicated 2 × 2 Latin square design. Steers were fed the same CON or HU diet used in Exp. 1 ad libitum once daily. Differences in the PDC index were used as indicators of differences in microbial CP synthesis. Ruminal pH, OM intake, and starch and CP digestibility were not affected by treatment (P ≥ 0.13). Digestibility of OM and NDF and ruminal concentration of ammonia-N and total VFA were greater (P ≤ 0.04) for the HU diet compared with the CON diet. The PDC index was similar (P = 0.81) between treatments at 2 h before feed delivery: 4% lower and 14% greater for the HU diet compared with the CON diet at 4 and 10 h after feed delivery, respectively (P < 0.01). These results suggest that, due to limited DIP supplied by a DRC- and HMC-based feedlot diet containing 20% DDGS, urea supplementation resulted in improved ruminal fermentation and feed digestibility, which may explain the concurrently improved cattle performance.